Changes on the Temporal Patterns of Ichthyoplankton Assemblages in the Çanakkale Strait, Türkiye - İsmail Burak Daban; Oğuzhan Ayaz; Ali İşmen (Çanakkale Onsekiz Mart University Journal of Marine Sciences and Fisheries)
Monitoring studies in a particular area after a long period of time can provide opportunities to understand environmental, physical and biological events that have occurred over time. From this point of view, we aimed to reveal ichthyoplankton assemblages in the Çanakkale Strait after 10 year period. Our findings indicated a 3 oC difference in sea surface termperature in the late spring and early winter compared to earlier studies. As expected, the highest mean abundance and biodiversity of ichthyoplankton were found in the late spring-early summer period but they showed rapid fluctuations even in consecutive weeks. Coastal resident species such as Diplodus annularis, Gobius niger, and Spicara maena were found to be abundant. In Çanakale Strait, larvae of mesopelagic species were sampled for the first time in this study. The occurrence of mesopelagic species far from their natal habitat in the northern Aegean deep sea trench may indicate a change in the region's hydrodynamics.